Persepsi Masyarakat Terhadap Layanan Badan Penyelenggara Jaminan Sosial Kesehatan di RSUD Morangan Sleman DIY - Herman Rante; Dyah Mutiarin (Journal of Governance and Public Policy, 2016)
Act No. 24 of 2011 is in force since one January 2014 throughout the local government, is no exception SlemanYogyakarta. However, implementation of this BPJS still encountered many problems in the field. But the boomingcommunity participation has not been matched by an adequate system so much going problems field. Moreover, lackof socialization by BPJS cause the crux of information in society. In addition, a lot of complaints from health insuranceparticipants who feel lost its facilities, especially in the referral process, medicines and other support services. Thepurpose of this study was to determine how the implementation BPJS Sleman district in managing the National HealthInsurance in Sleman. This research is descriptive quantitative research. Data collection techniques in this study questionnaireand documentation techniques. As for the number of samples in this study were 100 people with purposivesampling technique. The technique used to analyze the data in this study is the analysis technique by using the indexand Test Independent Sample T test using SPSS software. Based on the results of this study concluded that the publicperception of the Institution of Social Security ministry of health in hospitals Morangan Sleman Yogyakarta based onArticle 10 of Act No. 24 of 2011 which consists of 1) Conduct and / or receiving Participant registration, 2) Pickingup and collecting dues from participants and Employers, 3) Receive contribution of Government assistance, 4) Collectand manage data participants Social Security program, 5) Paying Benefits and / or pay for health services in accordancewith the provisions of the Social Security program and 6) Provide information regarding the conduct of theSocial Security program the participants and the community has been good with a range of index values of 2.78 s / d3.43. The results of this study also concluded that 1) there was no significant difference in perception between thegroups of beneficiaries and the contribution of non beneficiaries of contributions based on the implementation and oraccept registration of participants in the Health BPJS Sleman.2) there was no significant difference in perceptionbetween the groups receiving communities tuition assistance and contribution of non beneficiaries based data managementBPJS participants in Sleman. 3) there are significant differences in perceptions between groups of beneficiariesdues and non-beneficiary communities dues by the payment of benefits or pay for health services BPJS in Slemanand 4) there are significant differences in perceptions between groups of beneficiaries and the contribution of nonbeneficiaries dues based on the implementation of information provision BPJS Sleman